Broadband, large-numerical-aperture and high-efficiency microwave metalens by using a double-layer transmissive metasurface. (6th January 2022) - Liu, Yong-Qiang; Ren, Zhongru; Shu, Yingchao; Wu, Lujun; Sun, Jinhai; Cai, He; Zhang, Xutao; Lu, Lan; Qi, Kainan; Li, Liangsheng; Che, Yongxing; Yin, Hongcheng
Abstract: Broadband metalenses consisting of sub-wavelength phase gradient elements are indispensable in modern science and technology. So far, several broadband optical metalenses are demonstrated but mostly with either small NA or relatively low focusing efficiency. Herein, an ultra-thin broadband microwave metalens (frequency range from 8.0 to 10.5 GHz) with a relatively high-efficiency above 40% and a large NA of more than 0.6 is presented. The metalens is also fabricated and the measurement results agree with the simulations very well. The performances of the presented broadband metalens can surpass nowadays microwave metalenses largely and open up new vistas for low-profile, low-cost and light-weight microwave components.